Peritraumatic distress and its relationship to appliance-related orthodontic emergencies in orthodontic patients during the COVID-19 lockdown in Shanghai, China: a cross-sectional study - Jie Zhang; Kai Liu; Xin Yang; Shuting Zhang; Li’an Yang; Yuhsin Choi; Wa Li; Pei Tang; Jianyong Wu (BMJ Open)
Objectives The primary objective was to determine peritraumatic distress among orthodontic patients during the COVID-19 lockdown. And the secondary objective was to determine the relationship between peritraumatic distress in relation to different appliance types.Design Cross-sectional study.Setting Primary hospital between May and June 2022.Participants Patients in the process of orthodontic treatment, able to read Mandarin online, provided informed consent for the use of the data recorded and completed the questionnaire within a reasonable time.Interventions None.Primary and secondary outcome measures The demographic information and orthodontic urgencies were collected using online questionnaires. The peritraumatic distress symptoms were assessed by the COVID-19 Peritraumatic Distress Index (CPDI). The temporomandibular joint (TMJ) pain was evaluated using a Visual Analogue Scale.Results A total of 480 participants were enrolled, including 331 with fixed appliances, 131 with clear aligners and 18 with removable appliances. For all participants, the median CPDI score was 12 (4, 19). Higher CPDI scores were observed in participants with urgency (14 (6, 21) vs 8 (2, 15), p<0.001), participants aged ≥18 years (15 (6, 23) vs 8 (2, 15), p<0.001) and participants with TMJ pain (15 (8, 24) vs 11 (3, 18), p<0.001). Linear regression showed that age >18 years (β=0.271, p<0.001), TMJ pain (β=0.169, p<0.001) and urgency (β=0.144, p=0.001) were independently associated with the mean CPDI score.Conclusions The study suggested that during catastrophic events such as the COVID-19 lockdown, orthodontic urgencies may exacerbate patients’ peritraumatic distress, especially among adult patients and those who suffer from TMJ pain.